Increased FOXL2 expression alters uterine structures and functions. Issue 5 (25th August 2020) - Li, Rong; Wu, San-Pin; Zhou, Lecong; Nicol, Barbara; Lydon, John P; Yao, Humphrey H-C; DeMayo, Francesco J
Abstract: The transcription factor forkhead box L2 (FOXL2) regulates sex differentiation and reproductive function. Elevated levels of this transcription factor have been observed in the diseases of the uterus, such as endometriosis. However, the impact of elevated FOXL2 expression on uterine physiology remains unknown. In order to determine the consequences of altered FOXL2 in the female reproductive axis, we generated mice with over-expression of FOXL2 (FOXL2 OE ) by crossing Foxl2 LsL/+ with the Progesterone receptor Pgr cre model. FOXL2 OE uterus showed severe morphological abnormality including abnormal epithelial stratification, blunted adenogenesis, increased endometrial fibrosis, and disrupted myometrial morphology. In contrast, increasing FOXL2 levels specifically in uterine epithelium by crossing the Foxl2 LsL/+ with the lactoferrin Ltf icre mice resulted in the eFOXL2 OE mice with uterine epithelial stratification but without defects in endometrial fibrosis and adenogenesis, demonstrating a role of the endometrial stroma in the uterine abnormalities of the FOXL2 OE mice. Transcriptomic analysis of 12 weeks old Pgr cre and FOXL2 OE uterus at diestrus stage showed multiple signaling pathways related with cellular matrix, wnt/β-catenin, and altered cell cycle. Furthermore, we found FOXL2 OE mice were sterile. The infertility was caused in part by a disruption of the hypophyseal ovarian axis resulting in an anovulatory phenotype. The FOXL2 OE mice failed to show decidual responses during artificial decidualization in ovariectomized mice demonstrating the uterine contribution to the infertility phenotype. These data support that aberrantly increased FOXL2 expressions in the female reproductive tract can disrupt ovarian and uterine functions. Abstract : FOXL2 overexpression in the uterus induced epithelial stratification, blunted adenogenesis, increased fibrosis, and disrupted myometrium leading to impaired decidual responses.